Development of Oral, Potent, and Selective CK1α Degraders for AML Therapy - Huang, Lu; Chen, Lu; Chen, Lu; Peng, Bo; Zhou, Lixin; Sun, Yanli; Shi, Taiting; Lu, Jiayi; Lin, Weiye; Liu, Yuhang; Cao, Linhui; Li, Lanlan; et al. (JACS Au, 2024)
Molecular glue degraders (MGDs) are proximity-inducing agents that mediate the cooperative interaction between a target protein and an E3 ligase, introducing an additional layer of specificity beyond that afforded by traditional small molecules. Historically, molecular glues that stabilize protein–protein interactions were often discovered serendipitously. In this study, we leveraged the reprogramming potential of cereblon (CRBN)-based ligands and conducted a CRBN-dependent proliferation screen to identify CRBN-based MGDs capable of inducing the degradation of proteins essential for cell viability. Through our screening and subsequent medicinal chemistry optimization, we identified dCK1α-1 as a potent and selective CK1α-targeting molecular glue degrader. Furthermore, we synthesized an orally active derivative, dCK1α-2, with enhanced pharmacokinetic properties, which exhibited pronounced degradation activity and demonstrated efficacy in mouse models following oral gavage. These findings indicate that phenotypic drug discovery campaigns, in combination with chemically distinct CRBN ligand libraries, can accelerate the development of therapeutically relevant MGDs. Furthermore, the development of dCK1α-1 and dCK1α-2 provides new therapeutic options for cancers with functional p53 signaling and offers valuable chemical tools for future investigations into the role of CK1α.